Decarbonizing Canada's remote microgrids. (1st February 2023) - Stringer, Thomas; Joanis, Marcelin
Abstract: Canada produces most of its electricity using renewables. However, in remote communities that are not connected to Southern Canada's main grid, the quasi-totality of microgrids rely on fossil fuels to ensure electricity supply. How much would it cost to decarbonize all of these microgrids? This paper uses a cost-based approach paired with a binary integer optimization model to find the least costly decarbonization solution for each off-grid settlement from now until 2050. By using wind speed and solar irradiance data together with future generation and storage cost estimates, our model determines whether solar or wind is more appropriate for a settlement and at which period it is best to undergo a transition from fossil fuel generation to renewables. Our results show that the cost of decarbonizing Canada's remote microgrids is not prohibitive and which technology and implementation period are cheapest for each settlement. We find that in 2020 wind turbines would be the cheapest option for most settlements, whereas in 2050 solar panels would be the cheapest option for most settlements. Settlements that currently use diesel of heavy fuel to produce electricity should consider undergoing decarbonization as soon as possible, while those that use natural gas could wait until production and storage technologies become cheaper. Larger settlements and fly-in communities could also be prioritized. Highlights: Most remote communities in Canada still use fossil fuels to produce electricity. Decarbonizing Canada's remote microgrids would not be overly costly. The choice of wind or solar depends on the year of decarbonization. Larger settlements and fly-in settlements should be prioritized.